2019
DOI: 10.2737/iitf-gtr-50
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Inventory of Protected Areas and other Land Conservation Mechanisms in Puerto Rico

Abstract: The Forest Service, an agency of the U.S. Department of Agriculture (USDA) is dedicated to the principle of multiple use management of the Nation's forest resources for sustained yields of wood, water, forage, wildlife, and recreation. Through forestry research, cooperation with the States and private forest owners, and management of the national forests and national grasslands, it strives-as directed by Congressto provide increasingly greater service to a growing Nation.USDA prohibits discrimination in all it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Our model confirmed that Guánica Forest remains the most important protected area for the Nightjar while highlighting the fact that 45.3% of The most extensive tracts of continuous forest outside Guánica Forest are found in the region of Guayanilla-Peñuelas-Ponce (Figure 3). Protection of dry forests in this portion of the Nightjar's range may represent the greatest conservation priority for the species at present, considering the quality and extent of forest cover and virtual lack of protected areas in the region (García et al 2005, Castro-Prieto et al 2019. Moreover, private lands on the northeastern boundaries of Guánica Forest and the southern limits of Susúa Forest include remaining tracts of mature dry limestone forest (Vilella and Zwank 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model confirmed that Guánica Forest remains the most important protected area for the Nightjar while highlighting the fact that 45.3% of The most extensive tracts of continuous forest outside Guánica Forest are found in the region of Guayanilla-Peñuelas-Ponce (Figure 3). Protection of dry forests in this portion of the Nightjar's range may represent the greatest conservation priority for the species at present, considering the quality and extent of forest cover and virtual lack of protected areas in the region (García et al 2005, Castro-Prieto et al 2019. Moreover, private lands on the northeastern boundaries of Guánica Forest and the southern limits of Susúa Forest include remaining tracts of mature dry limestone forest (Vilella and Zwank 1993).…”
Section: Discussionmentioning
confidence: 99%
“…While some of these sites were located in areas with a great degree of fragmentation, they may serve as Nightjar habitat refugia and may have restoration potential (Shafer 1995). Presently, approximately 16% of Puerto Rico is designated as protected natural areas for conservation (Castro-Prieto et al 2019). Protection and restoration of forest fragments across the southern coast of Puerto Rico would help to ensure long-term persistence of the Nightjar across a considerable portion of its range (Beier and Noss 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several user-friendly R packages are available to create species distribution models. Given the speed of projected climatic changes, the variability in species-level responses, and the fact that only 12% of the Earth's surface (and 16% in Puerto Rico;Castro-Prieto et al 2019) is currently under some form of legal protection (Jenkins and Joppa 2009;Joppa and Pfaff 2011), effective conservation actions will also likely require efforts to systematically improve the extent, frequency, and duration of longterm monitoring of fauna.…”
Section: Discussionmentioning
confidence: 99%
“…Some protected areas in Puerto Rico provide always-suitable habitats for many bird and frog species, helping to conserve these species in a future, which may include extreme climate change. Nevertheless, long-term protection of these species may not be successful given that (1) regions with a high number of overlapping ASA species are relatively small, (2) protected areas are small and sparse (Castro et al 2019), and (3) large portion (~ 80%) of always-suitable areas is currently outside protected areas. Focusing special attention to the large proportion of always suitable areas currently outside protected areas may be effective in planning investments for regional conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation